Analisis Customer Service Dan Kepuasan Pelanggan Berpengruh Pada Penggunaan Livin By Mandiri KCP Jayapura - Ade Irma Srem; Lina Marlina (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2022)
The purpose of this study is to see if customer service and satisfaction are influenced by products. Independent? and Does customer service, in this case the application of technology, and product variations together have an effect on customer satisfaction with Life by Products? Independent? The study was conducted at Bank Mandiri KCP Jayapura Sentra Bisnis using a sample of 104 respondents and the saturated sample technique. This study uses the SPSS.27 statistical test tool to test the validity, reliability, and classical assumption tests (normality test, heteroscedasticity test, and multicollinearity test) and uses multiple regression analysis (t test and F test). The results of the statistical test state that the test results The t-count on the Customer Service Variable (X1) has a significance value of 0.009, the Technology Application Application Variable (X2) has a significance value of 0.000, and the Product Variation (X3) has a significance value of 0.029. From the results of the t-test, all independent variables have a significance level > 0.05%, meaning that The three independent variables have a simultaneous positive effect on customer satisfaction in Living by Products. Independent. Then, in the calculated F test, the results of the statistical test state that the Customer Service Variable (X1), Technology Application Application Variable (X2), and Product Variation Variable (X3) state that the calculated F value is 46,798 with the resulting significance value of 0.000b, which is less than 0.05%, meaning that the independent variables jointly have a positive effect on the independent variable, namely Customer Satisfaction with Living by Products. Independent Keywords: customer service, application of technology, product variations, and customer satisfaction